Nurses of Asia: Reflection from Asian Oncology Nursing Society Conference 2015 - Jimvert I Camarillo (Elsevier, 2016)
Another significant milestone from the Executive Board and the Organizing Committee of the Asian Oncology Nursing Society (AONS) transpired last November 20-21, 2015. The 2 nd AONS Conference was held in Seoul, South Korea under the theme of "Flying the Spirits of Asian Oncology Nursing." A total of 687 delegates from USA, Canada, Australia, Romania, and Asian Region supported this groundbreaking event. The objective of this 2-day conference was to facilitate sharing of expertise in the field of oncology nursing from the academe to clinical practice and to research. The issues that have been discussed in this 2-day symposium were Professional Development of Oncology Nursing, Quality of Life, Putting Evidence into Practice, Nursing Research, and Health Insurance for Cancer Care in Asia.